A Reaction-diffusion System of a Prey with Three Genotypes and a Predator (Journal of Partial Differential Equations, 1994)
The global existence and the asymptotic behavior of solutions to a reaction-diffusion system of a prey with three genotypes and a predator are considered. We establish the evolvement of a pure strain. Here an assumption concerning the diffusion is needed.
Keywords: Reaction-diffusion system; predator-prey model; genotype; asymptotic behavior